Improved Seismic Stratigraphy of the Mesozoic Weddell Sea - Rogenhagen, Johannes; Jokat, Wilfried; Hinz, Karl; Kristoffersen, Yngve (Marine Geophysical Researches, 2004)
We present a compilation of more than 45,000 km of multichannel seismic data acquired in the last three decades in the Weddell Sea. In accordance with recent tectonic models and available drillhole information, a consistent stratigraphic model for depositional units W1–W5 is set up. In conjunction with existing aeromagnetic data, a chronostratigraphic timetable is compiled and units W1.5, W2 and W3 are tentatively dated to have ages of between 136 Ma and 114 Ma. The age of W3 is not well constrained, but might be younger than 114 Ma. The data indicate that the thickest sediments are present in the western and southern Weddell Sea. These areas formed the earliest basins in the Weddell Sea and so the distribution of Mesozoic sediments is in accordance with the tectonic development of the ocean basin. In terms of Cenozoic glacial sediments, the largest depocenters are situated in front of the Filchner–Ronne Shelf, i.e. at the Crary Fan, with a thickness of up to 3 km.
Keywords: Antarktis; Weddellhavet; geofysikk; oseanografi; seismologi; stratigrafi; tektonikk

The ANTOSTRAT Legacy: Science Collaboration and International Transparency in Potential Marine Mineral Resource Exploitation of Antarctica - Cooper, Alan; Barker, Peter; Barrett, Peter; Behrendt, John; Brancolini, Giuliano; Childs, Jonathan; Escutia, Carlota; Jokat, Wilfried; Kristoffersen, Yngve; Leitchenkov, German; Stagg, Howard; Tanahashi, Manabu; et al. (Science Diplomacy: Antarctica, Science, and the Governance of International Spaces, 2011)
Keywords: Antarktis; geopolitikk; internasjonal samarbeid; marin geologi; mineraler; ressurser; stratigrafi; tektonikk